Is There a Difference in Outcome of Conversion Total Joint Arthroplasty When Staged Versus Concurrent Hardware Removal Is Performed? - Abbaszadeh, Ahmad; Llinas, Adolfo; Longo, Umile Giuseppe; Lizarraga, Marcelo; Restrepo, Camilo; Parvizi, Javad (CHURCHILL LIVINGSTONE INC MEDICAL PUBLISHERS, 2025)
World Expert Meeting in Arthroplasty, Istanbul, TURKEY, AUG 30-31, 2024
Keywords: orthopaedics; arthroplasty; hardware removal; conversion; periprosthetic infection